PEMANFAATAN TEHNOLOGI INFORMASI,SISTEM INFORMASI AKUNTANSI, INOVASI PRODUK, DAN LAPORAN KEUANGAN BERPENGARUH TERHADAP PENINGKATAN PENJUALAN UMKM DESA KEDIRI SELATAN KECAMATAN KEDIRI LOMBOK BARAT - KARTINI, ENDANG; MIMBAR, LALU; IZRAWATI, IZRAWATI (Universitas Mahasaraswati K. Mataram, 2024)
The aim of the research is to determine whether the use of information technology, accounting information systems, innovation and financial reports have a significant effect both individually and simultaneously on increasing MSME sales in South Kediri Village, Kediri District, West Lombok. The population, namely all MSMEs still active at the end of the 2023 period, is 287 MSMEs and the sample is 74 respondentsThe research results show that the calculated F value is 40.153 with a probability of 0.000, a probability value much smaller than 0.05. It was concluded that the four independent variables each had an effect, either partially or simultaneously, on increasing MSME business results. The regression equation Constant Value (α) of 0.262 is stated that if the independent variables are considered constant, then the average increase in sales is 0.262 units assuming the four variables are in a constant or fixed state. Utilization of Information Technology, amounting to 0.053, a positive value, which means there is a direct relationship with increasing sales of MSMEs. Likewise, the regression coefficients for SIA, IP, and Financial Reports are respectively 0.642, 0.118, and 0.238. The positive coefficient values mean that there is a unidirectional relationship with increasing sales. Furthermore, the correlation relationship between variables is very strong as indicated by the R value of 83.8%, while the adjusted R2 value is 0.685 (68.5%) and the variation in sales increase is explained by the independent variable. Where the remainder (100%-68.5%) = 31.5% is explained by other causes outside the model. Standard Error of estimate (SEE) is 0.246. The smaller the SEE value, the more accurate the regression model will be in predicting the dependent variable, namely Increased Sales for MSME players